1987
DOI: 10.1111/j.1600-0447.1987.tb02836.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems in communication in transcultural psychiatry

Abstract: It is often difficult for people from different cultural backgrounds to understand one another. On the other hand, this article provides some information about the problems Ethiopians have in understanding the concepts of Western psychiatry. In this study, the Western concepts are contained specifically in the items of the Self-Reporting Questionnaire, a psychiatric case-finding instrument designed by the World Health Organization. On the other hand, this article illustrates how Western-trained health workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…The congruity and comprehensibility of each answer was tested and the intra-rater reliability assessed (test-retest after 15 days): a mean K value for each item which was invariably 1 0.75 was evidentiated. Subsequent to testing, the SRQ proved to be sufficiently comprehensible and reliable, contrary to previous results obtained in some African settings [18], although an excess of affirmative answers was found to 'psychotic' items (33%). This was interpreted as the effect of typical cultural beliefs, such as those regarding thought influence and premonitory voices, more than an indication of substantial psychotic symptoms.…”
Section: Instrumentscontrasting
confidence: 98%
See 1 more Smart Citation
“…The congruity and comprehensibility of each answer was tested and the intra-rater reliability assessed (test-retest after 15 days): a mean K value for each item which was invariably 1 0.75 was evidentiated. Subsequent to testing, the SRQ proved to be sufficiently comprehensible and reliable, contrary to previous results obtained in some African settings [18], although an excess of affirmative answers was found to 'psychotic' items (33%). This was interpreted as the effect of typical cultural beliefs, such as those regarding thought influence and premonitory voices, more than an indication of substantial psychotic symptoms.…”
Section: Instrumentscontrasting
confidence: 98%
“…No significant difference was found in 'psychosomatic symptoms' (items 1, 2, 7, 19), in items regarding physical energy (13,18,20), core depressive items (9,11,15), psychic anxiety and fear (items 4, 6) or in items regarding cognitive performances (8,9). Positive answers to the item concerning an external attribution of their uneasiness (item 21 modified) were more frequently found in depressed housewives (75 vs. 10% of nondepressed dressmakers, Fisher's exact test p !…”
Section: Resultsmentioning
confidence: 89%
“…Edgerton [26] found that psychosis is not always attributed to witchcraft, and it was often regarded as an illness occurring for no reason or as the ‘natural result of life stress’. In the literature on local aetiological beliefs with regards to psychotic disorders in Africa, a wide range of factors have been described, such as substance misuse [31], nutritional factors [32], diseases of the blood [33], malaria [24] and ‘ worms in the brain’ [26] In this study, most of these factors were mentioned by the respondents, but there was variance between the settings. Among the Luo (arguably the setting that has been least influenced by monotheistic religions), spiritual causes were more prominent.…”
Section: Discussionmentioning
confidence: 90%
“…[6,7,15–19] Kortmann [15] had difficulties with the Amharic translation of the Self-Reporting Questionnaire (SRQ) in Ethiopia; more than one in four (26%) of affirmative responses proved invalid due to double-barreled questions, motivational biases, or a lack of conceptual congruity. Two items, “have you noticed any interference or anything else unusual with your thinking?” and “do you ever hear voices without knowing where they are coming from or which other people cannot hear?” are both long and have more than one question embedded within them, which made them difficult for respondents to understand and answer.…”
Section: Resultsmentioning
confidence: 99%